Respuesta :
m + 2m - 6 = -12 + 2m
3m - 6 = -12 + 2m
+6 +6
--------------------------------
3m = -6 + 2m
-2m -2m
-----------------------
1m = -6
/1 /1
m = -6
3m - 6 = -12 + 2m
+6 +6
--------------------------------
3m = -6 + 2m
-2m -2m
-----------------------
1m = -6
/1 /1
m = -6
To find the value of the variable m;
m + 2m - 6 = -12 + 2m
3m - 6 = -12 + 2m (combined like terms)
3m - 2m - 6 = -12 + 2m - 2m (subtracted 2m on both sides)
m - 6 + 6 = -12 + 6 ( added 6 on both sides)
m = -6
Hope this helps :)
m + 2m - 6 = -12 + 2m
3m - 6 = -12 + 2m (combined like terms)
3m - 2m - 6 = -12 + 2m - 2m (subtracted 2m on both sides)
m - 6 + 6 = -12 + 6 ( added 6 on both sides)
m = -6
Hope this helps :)